The real thing? Adaptations, transformations and burlesques of Shakespeare, historic and post-modern - Manfred Draudt (Ilha do Desterro)
The practice of adapting great authors to fit current requirements is not just a recent phenomenon. The first great wave of adaptations of Shakespeare came after the period of the closing of theatres in 1642, with the advent of the Restoration in 1660. Political change was accompanied by a radical change in tastes, ideals and conditions: theatres were roofed in and artificially illuminated (like the earlier private theatres); there was also elaborate changeable scenery; and for the first time female roles were taken by professional actresses. Most importantly, French neo-classicism was adopted as the fashionable theory that shaped both the form and the language of plays.